Perancangan User Experience Aplikasi Mobile Pemesanan Tiket Pendakian Semeru menggunakan Metode Human-Centered Design - Rizqi Ahmad Abdillah; Satrio Hadi Wijoyo; Intan Sartika Eris Maghfiroh (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Mount Semeru is one of the famously known mountains to hikers. A new policy is given by the authorized administrators effective from 2017, stating Semeru hiking reservations can only be made through the official reservation site available. However, the hiking reservation's procedure on the official site still feels troublesome and prolonged. Design of User Experience on Semeru Hiking Reservation Mobile Application has been directed using the Human Centered-Design (HCD) method. The first step is to analyze user requirements with the intention of specifying user needs and complaints. The next step is to design the solutions based on the user requirements. The outcome of this step is as follows: an information architecture as the development's guidance, a wireframe as the simple layout sketch, and a high-fidelity prototype as the interactive system resembling the completed application. The last step is to evaluate the prototype using the User Experience Questionnaire (UEQ) method. Based on the results, the prototype receives the mean value of 2,3 on pragmatic quality, 2,0 on hedonic quality, and 2,2 overall quality. The previously mentioned results fulfilled the minimum score of 0,8, thus can be categorized as excellent.